Pengaruh Penyuluhan Dagusibu Obat terhadap Tingkat Pengetahuan Kader Kb dan Kesehatan Desa Ambarketawang Gamping Sleman - Iramie Duma Kencana Irianto (Politeknik Kesehatan Bhakti Setya Indonesia, 2020)
The problem of using drugs is often found in Ambarketawang residents, residents do not understand how to use drugs properly, such as how to get, use, store, and dispose of drugs. This condition is thought to be due to the lack of knowledge of the residents about the medicinal chinsibu. It is important to give advice on medicinal dagusibu to residents so that they understand more about medicinal dagusibu. The purpose of this study was to determine the effect of counseling on increasing knowledge of family planning and health cadres in Ambarketawang Village and the distribution of knowledge levels about medicinal dagusibu. This type of research is pre-experimental with one group pretest-posttest design, namely the pretest-posttest design in one group. The population in this study were KB and Health Cadres of Ambarketawang Village as many as 275 people, with a sample of 37 cadres who came. Counseling was delivered between the pretest and posttest. Data collection using pretest and posttest questionnaires. The analysis in this study used the Wilcoxon Test. The Wilcoxon test on the results of the pretest and posttest obtained an Asymp.Sig (2-tailed) value of 0.000 or less than 0.05, which means that there is an increase in knowledge of chinsibu drugs in respondents after being given counseling. The Wilcoxon ranking proves that there are 32 out of 37 respondents whose scores increased after receiving counseling. The distribution of knowledge levels based on good, sufficient, and poor categories also showed positive changes, the percentage of respondents in the good category from 5% to 59.5%, the sufficient category from 15% to 27%, and the less than 17% category to 13.5%. This means that the research objective to determine the effect of counseling on increasing knowledge of family planning cadres and health in Ambarketawang Village was achieved.